Development of computer libraries capable of simulating emulsions using the Lattice-Boltzmann method (2011)
Emulsions are of interest at an industrial level due to the properties obtained with these mixtures. Microscopic analysis is of interest to the understanding of emulsions to accomplish a deeper understanding in this subject. A program capable of simulating the behavior of an emulsion was developed using programming language Python. The general framework of the Lattice-Boltzmann Method is used while adding the Shan and Chen model for multi-component fluids. The simulation of superficial tension, drop deformation and the principal mechanisms of coalescence are studied and predictions on what is happening in an emulsion are discussed. Comparisons are also made with what is found on literature and limitations on the code are explained.